The Influence of Mobile Applications on Online Shopping Habits in Indonesia - Autar, Nailil (Journal Mobile Technologies (JMS), 2024)
This study examines how mobile applications influence online shopping behavior among Indonesian consumers within an increasingly digitalized economy. Drawing on the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT2), and consumer behavior perspectives, the research investigates how perceived usefulness, ease of use, hedonic motivation, social influence, and habitual engagement shape purchasing behavior. Using a quantitative approach, data were collected from 350 active users of mobile commerce platforms such as Shopee, Tokopedia, and Lazada. Regression analysis revealed that hedonic motivation exerts the strongest influence on purchase frequency, followed by perceived usefulness and habitual usage, while ease of use and social influence also contribute significantly. The findings suggest that mobile shopping in Indonesia has evolved from a transactional activity into a leisure-oriented experience, shaped by emotional gratification, convenience, and social engagement. The study concludes that mobile commerce represents not only technological progress but also a behavioral and cultural transformation, redefining consumption as a blend of pleasure, efficiency, and identity expression. Future research is recommended to explore emotional, ethical, and generational aspects of digital consumption through qualitative and longitudinal approaches.